How to write abstract for a scientific journal article - Shah, Jay N (Journal of Patan Academy of Health Sciences, 2017)
Abstract is the ‘mini article’. It provides the background, the context, the purpose of the study. Briefly it describes the methods- where, how the participants were recruited, study design, variables studied, analytical methods and ethical issues. The findings are in line with the objectives and methods and its significance to draw the conclusions. The key words are listed at the end, in the journal style. Abstract is indexed and freely available. Thus, the information must confer to text.There is a word limit, usually of 250 words. Thus it requires time and skill to include important information with logical flow to ‘capture’ the essence of full article. The ‘copy-paste’ of sections from the main content should not be done because there is word limit. For example, there are only two to three lines of 20-30 words space for the ‘background’ in the abstract, unlike the 150 to 200 words for introduction section in the main article. Majority of readers, as much as three quarters, read only abstract after scanning for the title, and do not proceed to read full article due to unavailability of free-full-text or simply too many articles available on the net. Thus, abstract should contain as much information as possible in a concise form. Many non-English language journals publish abstract in English, which are indexed on various repository. Thus it is important to give time to write abstract, to ‘hook’ the readers and peers as well as increase visibility of the article. Even though, abstract appears at the beginning of the manuscript, it should be written when the article writing is completed. This allows elaborating upon key aspects of the paper, yet being concise, to help readers ‘want’ to read the rest of the paper.There is often a question, especially for the beginners, to decide how much information is enough in the abstract. This is not that difficult to comprehend; a simple logic is consider- ‘if the abstract is the only part of the paper accessible’, it the story complete? As a reader or peer, are you happy with the amount of information, and if the answer is "no" then it has to be revised. The information in the abstract must make sense of the full article.